2002
DOI: 10.1099/0022-1317-83-7-1721
|View full text |Cite
|
Sign up to set email alerts
|

Open reading frame sequence of an Asian enterovirus 73 strain reveals that the prototype from California is recombinant

Abstract: Phylogenetic analysis within the VP1 region now enables molecular typing of enteroviruses consistent with neutralization results. Three untypable isolates, 2776/82, 57/99 and 22/00, from Korea, North India and Bangladesh, respectively, showed within this region 98.0-99.0% amino acid identities. These were less than 77% to the previous enterovirus prototypes, but 91.5-92.5% to CA55-1988, the recently identified enterovirus 73 (EV73) prototype from California. All three strains were, however, most similar to CA6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…The evolution of enteroviruses occurs through genetic drift and, over much longer periods, antigenic diversification in the structural gene region encoding the virus capsid (7,14,25,30,51,55); it may also occur by recombination between the capsid and nonstructural coding parts of the genome and the 5Ј untranslated region (2,13,16,20,26,28,29,35,39,41,47,48,53). To date, almost all documented examples of recombination have been limited to members of the same species (e.g., between species B serotypes), with the exception of the 5Ј untranslated region, where only a single genetic group can be identified within human species A and B and a second with species C and D (48).…”
Section: ؊3mentioning
confidence: 99%
“…The evolution of enteroviruses occurs through genetic drift and, over much longer periods, antigenic diversification in the structural gene region encoding the virus capsid (7,14,25,30,51,55); it may also occur by recombination between the capsid and nonstructural coding parts of the genome and the 5Ј untranslated region (2,13,16,20,26,28,29,35,39,41,47,48,53). To date, almost all documented examples of recombination have been limited to members of the same species (e.g., between species B serotypes), with the exception of the 5Ј untranslated region, where only a single genetic group can be identified within human species A and B and a second with species C and D (48).…”
Section: ؊3mentioning
confidence: 99%
“…Since then no new types have been reported until EV-73 was identified by molecular techniques in California and Oman (Oberste et al, 2001) and as imports into Sweden from South and East Asia (Norder et al, 2002). One reason for this is the labour-intensive conventional methods for establishing new enterovirus types, including the production of hyperimmune antisera and cross-testing against previous prototypes.…”
Section: Introductionmentioning
confidence: 99%
“…Complete genome sequences of 46 prototype strains of HRV-A and HRV-B have been generated recently (Kistler et al, 2007b;Tapparel et al, 2007). According to this limited set of HRV sequences, it has been suggested that the main force driving the genetic diversification of HRV may be genetic drift rather than intra-or interserotypic recombination, which, in contrast, are common in closely related HEV genomes (Brown et al, 2003;Lindberg et al, 2003;Norder et al, 2002;Santti et al, 1999). In HEV, the recombination sites are usually located in genomic regions encoding non-structural proteins, but have also occasionally been found in the VP1 capsid protein coding region Martin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%